2019
DOI: 10.1186/s12906-019-2537-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antibiotic-modifying activities of fractions and compounds from Albizia adianthifolia against MDR Gram-negative enteric bacteria

Abstract: Background Albizia adianthifolia (Schum.) is medicinally used in Cameroon to manage bronchitis and skin diseases. Our previous study documented the antibacterial potential of its roots’ methanol extract. In this study, methanol roots extract was subjected to chromatography techniques and fractions (AARa and AARb), sub-fractions (AARa1–4, AARb1–2 and AARb11–14) together with isolated phytochemicals were assessed for their antimicrobial as well as their antibiotic-potentiating effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Implausibly, both multidrug resistant and reference strains of E. coli were the most unresponsive strain of all tested bacteria species. These findings agreed with several reports [ 13 , 19 21 ] which demonstrated that gram positive ( S. aureus and E. faecalis ) bacteria to be more sensitive than gram negative ( E. coli and K. pneumonia ) bacteria for the plants’ phytochemical components being studied. Moreover, many studies have shown that medicinal plants contain different bioactive ingredients that inhibited the growth of human pathogenic bacteria [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Implausibly, both multidrug resistant and reference strains of E. coli were the most unresponsive strain of all tested bacteria species. These findings agreed with several reports [ 13 , 19 21 ] which demonstrated that gram positive ( S. aureus and E. faecalis ) bacteria to be more sensitive than gram negative ( E. coli and K. pneumonia ) bacteria for the plants’ phytochemical components being studied. Moreover, many studies have shown that medicinal plants contain different bioactive ingredients that inhibited the growth of human pathogenic bacteria [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…gigantean had inhibitory potential on all tested human pathogenic bacteria and fungi except T. rubrum [ 16 ] . Another study conducted on extracts of Carum copticum and Albizia adianthifolia had exhibited good antimicrobial activities against E. coli, Proteus species, P. aeruginosa, P. neumoniae and Salmonellae species [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of a recent study indicate that rumen microorganisms may degrade several cyanotoxins [33], the threat from cyanotoxins cannot be ignored. Our results revealed that BSS might inhibit the growth of cyanobacteria, since its antibacterial activity has been documented [34,35].…”
Section: Discussionmentioning
confidence: 61%
“…Indeed, in most of the countries where they grow, these plants are widely used in traditional medicine for the treatment of various diseases. As examples, Albizia adiantifolia was used for the treatment of syphilis [3] and bronchitis [4], Albizia schimperiana for the treatment of pneumonia [5] and diarrhea [6] and Albizia odoratissima for the treatment of dysentery and rhinitis [7]. Most research has shown that the antimicrobial activity of Albizia extracts [8,9] and several active ingredients were already isolated [10].…”
Section: Introductionmentioning
confidence: 99%